The Qurʼan and the human evolution: a scientific approach - Ahmed, Dildar (Paramount Publishing Enterprise Karachi, 2004)
The Qur'an and Human Evolution: A Scientific Approach explores the intersections between Qur'anic teachings and scientific theories of human evolution, offering a perspective that seeks harmony between faith and science.